The effects of time pressure and numerical unbalance on football players` interpersonal coordination and movement uncertainty - Demétrio, G.; Rochael, M.; Moura, F. A.; Bedo, B. L. S.; Praça, G. M. (International Journal of Performance Analysis in Sport, 2025)
The study compared interpersonal coordination (vector-coding technique) and movement uncertainty (Shannon Entropy) on the longitudinal and lateral axes during offensive and defensive phases among football small-sided games with (TP) and without time pressure (noTP), in numerical equality (NE) and numerical superiority (NS). Forty under-17 football players participated in the study. Positional data were obtained through GPS devices. Data between the conditions were compared using a multivariate analysis of variance (MANOVA) for interpersonal coordination and the Kruskal-Wallis test for entropy measures. Results showed higher in-phase time on the x-axis during defensive phases in TP+NE vs. noTP+NE (p = 0.037) and on the y-axis during offensive phases in TP+NE (p = 0.031) and noTP+NS (p = 0.023) vs. noTP+NE. Additionally, higher y-axis entropy in the defensive phase was observed in noTP+NE vs. TP+NE (p = 0.047). A higher entropy in the y-axis during the defensive phase was found in noPT+NE (p = 0.038) compared to other conditions. In conclusion, the presence of time pressure rules increased the percentage of time in the in-phase pattern on the y-axis during the offensive phase and on the x-axis during the defensive phase. Protocols without time pressure generated higher entropy values in the defensive phase.